Relationship of Clinical Manifestations and Results of Thorax Photo Examination in Diagnosing TB Complications: A Case Report - Mathias; Agustino Rosario Idong; Ayundari Angelia Febriany; Bonifasius Berkah Widodo; Danti Dja Jatnika; Leonardo Diogo; Sharon Felicia Alexandria Manik; Tiodora Arimenda Br Surbakti (Medical Clinical Update, 2023)
For more than 4,000 years, tuberculosis (TB) has plagued the human species. It is a persistentdisease caused by the bacillus Mycobacterium tuberculosis that spreads from person to personthrough the air. Although TB usually affects the lungs, it can also harm the vertebrae, brain, stomach, or kidneys. The symptoms of pulmonary tuberculosis can include a chronic cough, chest pain,hemoptysis, weakness or exhaustion, weight loss, temperature, and night chills. The lung x-ray hasbeen used to identify TB for more than a century. The overview's primary goal is to highlight theidentification of TB complications.